Improving Accountability and Transparency in Nonprofit Educational Organizations through the Implementation of ISAK 35 - Sistya Rachmawati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The implementation of community service and independent implementation of non-profit educational organizations plays an important role in providing quality educational services without a profit orientation. However, challenges in maintaining accountability and transparency still often occur, especially in terms of financial reporting. The application of Financial Accounting Standards Interpretation (ISAK) 35: Presentation of Financial Statements of Non-Profit Entities is a strategic step to ensure that the financial statements of non-profit educational institutions can reflect the actual conditions and are easily understood by stakeholders. This PKM activity aims to improve the understanding and implementation of ISAK 35 in non-profit educational institutions partnered with Trie Bhakti University through training, mentoring, and the preparation of ISAK 35-based financial report models. The results of this activity show a significant increase in the understanding of foundation administrators regarding the principles of accountability, financial report structure, and public information disclosure. With the implementation of ISAK 35, partner educational institutions are able to produce more transparent, relevant, and reliable financial reports as a form of accountability to the public and donors